Recent development of amino acids and peptides in metal ions detection: an overview - Abdull Manap, Mohd Rashidi; Yusof, Nor Azah; Mohd Nor, Siti Mariam; Ahmad @ Amat, Faujan (Oriental Scientific Publishing, 2010)
Little work has been reported on the development of solid state metal ion sensor based on the use of amino acids and peptides. This review covers literature on the use of amino acids and peptides (short peptide, oligopeptide and cyclic peptide) as a recognition molecule for metal detection system. Amino acids and peptides offer a high degree of selectivity, good limit of detection and high sensitivity towards detection of metal ion.